SafeWay: An Android Application based Automatic Vehicle Accident Detection and Messaging System - Bakhtawar, Shadma; Imam, Shahid; Ali, Shadab; Sunil, Sunil (International Journal of Computer Sciences and Engineering, 2026)
The research paper outlines the creation of vehicle accident detection and notification system that is based on an Android application. When a vehicle collision occurs, the system uses sensors and mobile technologies to notify the necessary parties, including emergency services, insurance providers, and worried family members. A predestined contact list will get an emergency alert message from the system when it has detected and appraise the relentlessness of a vehicle accident. The technology is proposed to be extremely accurate and effectual at detecting and responding to auto accidents. When a vehicle's velocity suddenly changes, the system employs a mix of accelerometer, gyroscope, and Global Positioning System (GPS) sensors to look for impending accident signs. After determining the accident's relentlessness using an algorithm, the system sends an emergency alert message to a predetermined contact list. The system has undergone testing and been shown to be reliable and successful in identifying vehicle collisions and transmitting emergency signals. The design and development of the system, its possible applications, and the benefits and difficulties of its adoption are all covered in the research paper. The paper also explores the possibility for more study to enhance the system